Antivenomics: a proteomics tool for studying the immunoreactivity of antivenoms - Calvete Chornet, Juan José (2015)
Envenoming following snakebite is largely a neglected threat to public health in tropical and subtropical regions of Africa, Asia, Latin America and Oceania addicting some of the world’s poorest rural communities. An estimated 5.5. Million people are bitten by sneakers each year, resulting in about 400 000 amputations, and between 20 000 and 125 000 deaths; however, the true scale of this “disease of poverty” may be much greater than these hospital-based statistics.